Non-coding RNAs in osteoarthritis and osteoporosis-related hip fractures: molecular biomarkers for precision diagnosis and prognosis - Zhang, Chengxuan; Chen, Yu; Zhang, Jian (Frontiers in Endocrinology, 2025)
As individuals age, bone density declines and the likelihood of fractures increases, particularly in women experiencing menopause. Hip fractures, the most severe consequence of osteoporosis, are becoming more common due to the aging global population and a 1-3% annual increase in hip fractures in most regions. The specific epigenetic mechanisms underlying the onset of osteoporosis and its related fractures remain predominantly unexamined. Research indicates that epigenetic modifications can elevate the risk of osteoarthritis, osteoporosis and bone fractures, especially hip fractures, by linking genetic predispositions with environmental factors. Essential regulatory components in these factors encompass microRNAs, lncRNAs, and circular RNAs. This review examines the function of miRNAs, lncRNAs, and circRNAs in the advancement of osteoporosis, with an emphasis on osteoblasts and osteoclasts. The objective is to enhance comprehension of RNA classes in osteoporotic hip fractures, which may facilitate early detection and prognosis, as well as clarify cellular interactions, potentially resulting in innovative diagnostic techniques and targeted therapies.